Захід України: критерії визначення кінця палеоліту і початку мезоліту - Мацкевий, Л.Г. (Археологія, 2001)
У статті аргументовано суттєві риси, які характерні для території заходу України наприкінці палеоліту, та ті риси, що вже знаменували нову історичну епоху — мезоліт. Еще в XIX в. палеолит и мезолит были выделены как эпохи. Однако и поныне рубеж между ними на территории запада Украины пока четко не установлен. Для конца палеолита — X тис. до н. э. (аллерёд) — в регионе наиболее характерны стоянки Молодовэ I и V, Осэливка I, Кормань IV, Жидачив I, Прийма I и Львив VII. Наиболее продуктивной была загонная (облавная) охота. Среди каменных орудий преобладают резцы, скребки, ножи, а в отдельных комплексах — острия-наконечники.
Для мезолита здесь характерны локальные культуры Нобэль-Кунын, Нэзвысько-Осэливка, Вороцив-Старуня и Камъяныця-Бараннэ (Мшана). Начало эпохи совпадает с началом голоцена (дриас III) и датируется IX тыс. до н.э. Уже нет крупных млекопитающих, преобладают животные средних и небольших размеров. Наиболее эффективной становится охота скрадыванием (из засады), хотя имела место как реликт и загонная. В пищевом балансе возрастает роль усложненного собирательства и рыболовства. Широко использовались лук и стрелы. Среди «фоновых» каменных орудий — скребки, резцы, ножи, скобели, наконечники стрел и геометрические микролиты типа трапеций, треугольников и сегментов. In the XIX century, the Paleolithic and Mesolithic ages were separated as epochs. But until now, the boundary between them has not been neatly determined on the territory of Western Ukraine. For the end of the Paleolithic age, the next sites in this region are most typical: Molodove I and V, Oselivka I, Korman’ IV, Zhydachiv I, Pryima I, and Lviv VII. There, the complex investigations allowed one to date the end of the Palaeolithic age by the X millennium BC (Allerod). The hunt with beaters (the round-up) was the most productive. Cutters, scrapers, knives, and, in some complexes, spikes-tips predominate.
For the Mesolithic age, the local cultures of Nobel’-Kunyn, Nezvysko-Oselivka, Vorotsiv- Starunya, and Kam’yanytsa-Baranne (Mshana) are typical here. The beginning of the epoch coincides with the beginning of the Holocene (Drias III) and is dated by the IX millennium BC. There were no big mammals, the little and mean animals predominated. The hunt by ambush became the most effective, but the hunt with beaters took place as a relic. The share of complicated gathering and fishing increased in food balance, and especially it occurred in regions that became free of the glacier. The bows and arrows were used broadly. Between the «background» stone tools, there were scrapers, cutters, knives, drawing-knives, arrow tips, and geometric microliths such as trapezia, triangles, and segments.